Systematic Literature Review, The Impact Of The Sholawat Nariyah Tradition In Indonesia On Changes In Community Social Behavior - Ismail, Ismail; Musyafa, Muhammad Hilmi; Choslan, Faizah (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2023)
Praying to the Prophet Muhammad (peace and blessings be upon him) is a recommendation from Allah to the believers. People who read a lot of Sholawat will get a great reward from Allah Swt. In fact, the Prophet said that even one Sholawat that is read will be rewarded tenfold by Allah. In addition to rewards, Sholawat also has many virtues. One of them is that Sholawat can be the cause of the descent of guidance to a servant. This virtue then makes Sholawat widely used as a means of proselytizing by da'i in guiding the community. They established assemblies and routines whose core activity was the recitation of Sholawat. One of the widely used Sholawat is Sholawat Nariyah. This article aims to see the extent of the impact of Sholawat Nariyah activities on changes in community social behavior. The method used is a Systematic Literature Review of previous studies contained in the Google Scholar data base with several keywords determined. The results obtained from the review are that Sholawat Nariyah activities have a huge impact on changes in people's social behavior. Many things are experienced by Sholawat Nariyah worshipers after participating in this activity which then gradually converts their social behavior from bad to better.